Craniofacial Fibrous Dysplasia: Presentation of 2 Cases and Literature Review: Fibrodisplasia Óssea Craniofacial: Apresentação de 2 Casos e Revisão da Literatura - Silva, Diana Pinto; Lima, António; Costa, Nuno; Vilarinho, Sérgio; Pinto, Afonso Almeida; Dias, Luís (Gazeta Médica, 2018)
A Craniofacial fibrous dysplasia is a rare congenital pathology of the bone, with predilection for craniofacial bones, frequently involving the nasal sinuses, orbit and skull base. The authors present 2 cases of craniofacial monostotic fibrous dysplasia and perform a brief revision of literature about this matter. The first case is a frontal fibrous dysplasia in a 20-year-old man, and the second case is about sphenoid fibrous dysplasia in a 65-year-old man. The first case, given the young age, growth and aesthetic repercussion, was submitted to surgery, without signs of relapse after one year of follow-up. The second one was an accidental finding in an older and asymptomatic man, reason why he underwent conservative treatment and observation. Both were multidisciplinary managed at our institution and show the variability of presentation, orientation and evolution of the same pathology.